Komering Culture Local Content Curriculum Implementation at Primary School - Musiman Musiman; Muhammad Kristiawan; Rambat Nur Sasongko (STAI Hubbulwathan Duri, 2022)
The Komering cultural local content curriculum was adopted at Muhammadiyah Primary School in 2021. The school is using the Komering cultural local content curriculum to help pupils comprehend local culture. However, the development of the local content curriculum in schools has not been founded on a scientific review of the curriculum, thus, teachers who carry out Komering cultural local content are still drawn from general instructors or do not have backgrounds in arts and culture education. As a result, the implementation is incomplete. The goal of this research was to find out what role educators had in the implementation of the Komering Culture Local Content Curriculum at Muhammadiyah Primary School. Local content instructors' grasp of Komering cultural knowledge, the learning process for Komering culture local content, and assessment of learning results. The method utilised is qualitative with a descriptive approach. The instrument employed observation and interviews, which were then evaluated using descriptive qualitative methods using Miles and Huberman’s theory. The findings revealed that the basic concerns of schools in implementing the Komering culture local content curriculum were based on the vision and goal of the local government, which conveyed regional culture and taught students more about Komering culture. Teachers back them as curriculum implementers for commercial, and cultural content in their own communities, and principals recognise them as leaders.